Evaluating Alcohol Exclusion Provisions in Health Insurance: Evidence from the Uniform Accident and Sickness Policy Provision Laws - Baris Yörük; Joseph J. Sabia; Dhaval M. Dave (Institute of Labor Economics (IZA), 2024)
Alcohol exclusion provisions, embedded in the Uniform Accident and Sickness Policy Provision Law (UPPL), allow health insurance providers to punish alcohol consumption by permitting them to deny claims for injuries stemming from alcohol impairment or the use of non-prescribed narcotics. Although the UPPLs were originally proposed to discourage excessive drinking and substance use, there is no clear evidence to either support or refute that these laws achieved their intended purpose. Furthermore, few studies document that these laws may have unintended consequences, as they create a disincentive for physicians to test the blood alcohol concentration (BAC) levels of injured patients due to concerns about potential insurance reimbursement denials. We provide a comprehensive analysis of the UPPLs by investigating their impact on alcohol consumption at the intensive and extensive margin, drunk driving behavior, alcohol-related traffic fatalities, alcohol-related crime, and health insurance coverage rates and premiums.
Keywords: I10; I18; 330; alcohol exclusion provisions; Uniform Accident and Sickness Policy Provision Law; alcohol consumption; alcohol consumption related outcomes